SIMULATION ANALYSIS OF RV REDUCER BOLT FORCE - DONG Wei; HAN Ju; WANG XiaoHu; ZHANG FuShuai (Jixie qiangdu)
The bolt is the main connecting part of the RV reducer. Its mechanical properties affect the transmission accuracy of the whole machine. According to the principle of generating the profile of the cycloidal gear. Combining vector method to establish the profile equation of cycloidal wheel after shaping. Apply the principle of deformation coordination. Mechanical analysis of each component of the whole machine. Calculate the force of the bolt in theory; Considering the modification of the cycloidal wheel and the diameter error of the center circle of the pin tooth. Multi-body dynamics analysis in ADAMS. Through simulation analysis,we can know: Different initial mounting angles or different angles of rotation. Different bolts have different trends and different degrees of change. Different angles of rotation. Bolt force is not in the same order. As the angle of rotation of the cycloid increases,the overall force of the bolt increases first and then decreases. As the load increases,the bolt is gradually increased in force. As the load increases,the magnitude of the increase also increases.